Jeroboam’s Wife: The Enduring Contributions of the Old Testament’s Least Known Women - Olojede, Funlola (Scriptura, 2009)
Approaching Old Testament narratives from the canonical perspective, Robin Gallaher Branch retells the stories of seven female characters who appear briefly in the Bible but whose contributions are considered unforgettable because not only did they change the course of history, their brief mention provides significant insight into the major characters with whom they are associated. The Bible mentions the names of three of the women - Miriam, the "pint-sized heroine" (p. 28); Rizpah who started out as "a pawn in the great game of kings" (p. 36) but ended up a silent activist (p. 60); and Athaliah, "daughter of a king, sister of a king, wife of a king, mother of a king" and later a queen in her own right (p. 159). The other four, the Wise Woman of Abel Beth Maacah, the Wife of Jeroboam, the Widow of Zarepath, and the Israelite Slave Girl (in 2 Kings 5) remain anonymous. Notably, some of the anonymous women are also silent e.g. Jeroboam’s wife, while the others have speaking roles e.g. the Wise Woman of Abel.